2019
DOI: 10.3390/atmos10020064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Element Concentrations (Ba, Mn, Pb, Sr, Zn) in the Bones and Teeth of Wild Ruminants from the West Carpathians and the Tian-Shan Mountains as Indicators of Air Pollution

Abstract: Through analyzing the concentrations of selected heavy metals (Ba, Mn, Pb, Sr, Zn) in the bones and teeth of wild living and ecologically equivalent ruminants from the Tian-Shan (Capra sibirica and Ovis ammon polii) and the West Carpathians (Rupicapra rupicapra tatrica) we compared the environmental pollution levels of these two mountain ranges. The samples were analyzed by X-ray fluorescence. Significantly higher contents of Zn and Mn as well as a higher frequency of measurable occurrences of Mn, Ba, and Pb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…The measured values of mercury in the feathers of the Carpathian eagle population did not significantly differ between the eagles which hunt in forests and those which hunt also in alpine zone. Our results are a bit inconsistent with large number of studies that describe animals inhabiting higher elevations as being exposed to higher concentrations of pollutants, mainly due to deposition of pollutants on mountain ridges (Ballová and Janiga 2018 ; Ballová et al 2019 ; Janiga et al 2019 ). One possible explanation is that forests tend to trap toxic metals from the atmosphere and thus provide protection from pollutants (Kocić et al 2014 ; Huang et al 2017 ).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The measured values of mercury in the feathers of the Carpathian eagle population did not significantly differ between the eagles which hunt in forests and those which hunt also in alpine zone. Our results are a bit inconsistent with large number of studies that describe animals inhabiting higher elevations as being exposed to higher concentrations of pollutants, mainly due to deposition of pollutants on mountain ridges (Ballová and Janiga 2018 ; Ballová et al 2019 ; Janiga et al 2019 ). One possible explanation is that forests tend to trap toxic metals from the atmosphere and thus provide protection from pollutants (Kocić et al 2014 ; Huang et al 2017 ).…”
Section: Resultscontrasting
confidence: 99%
“…The Western Carpathians, in which Slovakia is located, show higher levels of metal pollution (Ballová and Janiga 2018 ; Ballová et al 2019 ). Several studies confirmed our assumptions that heavy metal pollution in alpine mountain ranges located in the Western Carpathians is caused by long-distance transport of air pollution from Polish and Slovakian industrial locations (Camarero et al 2009 ; Janiga and Haas 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Concentrations of Pb and Cd in Vaccinium myrtillus, Luzula luzuloides and Dryopteris dilatata have mostly been found to exceed the limits of the natural occurrence of these elements in plants (Ciriaková, 2009 ). The alpine biota in the Tatras is probably under permanent, long-term stress from exposure to TMs, as suggested by the excessive amounts of Zn, Pb and Cd reported from the skulls, bones, and teeth of wild animals, such as snow voles, Tatra marmots and chamois (Ballová et al, 2019 ; Janiga & Haas, 2018 ; Janiga et al, 2019 ). However, the pollution of the TNP environment is primarily a sad remnant of the strong development of heavy industry and mining in Poland in the 1970s, with influxes of pollutants also taking place in later years.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study, no significant difference was found for lead concentrations in femur, tarsus, and feathers following exposure of chicken with three different levels of lead in the diet (Valera et al, 2017). The data ratios were determined as meaningful variables tors of exposure for wild animals (Ballova et al, 2019).…”
Section: Cartilage To Other Tissue Concentration Ratio (Cor) and Bone...mentioning
confidence: 99%
“…in Poland for 60 years(Gizejewska et al, 2020). In other cases, bone and teeth have been proposed as bioindicators of air pollution of lead in wild ruminants(Ballova et al, 2019). The higher C B of lead in the femur of 2.7 years-old wild bear was reported as 1.9 -12.5 µg.g -1(Lazarus et al, 2018).…”
mentioning
confidence: 99%